REGIONAL SELF-SUFFICIENCY: CHALLENGES AND SOLUTIONS - N. Kh. Tokaev; M. Sh. Basnukaev (Финансы: теория и практика)
The article deals with various issues associated with the adoption and execution of the regional budget. The deficit-free regional budget does not mean in modern Russia a full coverage of budgetary expenditures from its own budget revenues. Moreover, when the regional budget is adopted in a balanced form which does not mean achieving the full self-sufficiency due to certain restrictions, which are introduced on budgetary needs, and there are no grants, subsidies or subventions for them. It is a budgetary practice in Russia and its regions, it requires an appropriate study and consideration. Nowadays, while making decisions on expenditures funded by the regional budget, the authorities face many conflicting tasks needed to be solved. The most difficult problem is looking for new regional sources of budget revenues. However, there are also two kinds of restrictions in this area. First, the objective inability of the region’s economy to meet budget needs due to low rates of the financial balance of the economy. Second, the tax restrictions defined by all-Russian legislation and different tax regulatory regimes. Tax autonomy to the extent granted to the regions ‘cannot cope’ with such restrictions; it results in setting additional budget targets towards reducing costs or attracting financing in the form of grants, subventions and subsidies. The option of borrowing in the form of loans, has also its own pre-set restrictions.